Parental Involvement on Childrens Education What Works in Hong Kong - Ho, Esther Sui-Chu. (SpringerBriefs in Education, 2013)
This book is based on the empirical work of a large-scale project to investigate the possible impacts of diversified forms of parental involvement on children and school by first exploring through a series of ethnographic case studies how principals, teachers and parents perceive and act on parental involvement in the primary schools of Hong Kong and, then, examining how the different forms and levels of parental involvement are related to individual and institutional factors through a series of survey studies on all these stakeholders in childrens education. Finally, the book assesses the extent to which different forms of parental involvement affect student performance based on student survey results and available school records.